Islamic Parenting Untuk Anak Usia Golden Age - Cimba, Tisa Mori (Universitas Muhammadiyah Sumatera Utara, 2022)
Education is an important part of human life, education is like the blood that flows in life. Parents have a big responsibility for the education of their children, from the moment they are born humans need to have a strong foundation for their future life, the golden age is a time when parents can build a strong foundation for their children, because at this age children will go through a different phase. strong to see, hear and feel. Therefore, parents need to pay great attention to building the foundation of children's education at this golden age. There are several things that need to be considered in children's education, the first is religious education. Instilling a religious education parenting pattern for children or what we call Islamic Parenting is the first thing that parents need to pay attention to, because if at the golden age the foundation of education and parenting with Islamic values is not formed strongly, it will be difficult to fix it when he grows up. For this reason, the purpose of this study is to find out how the parenting pattern of Islamic education for children aged golden age and the method used in this study is a qualitative method with a literature review that will produce descriptive notes or data in the research text, the results of this study are in the form of information notes for knowledge about Islamic Parenting for children during the golden age.Keyword: Islamic Parenting, child, age, golden age